MORPHOLOGICAL AND HISTOLOGICAL CHANGES DURING SOMATIC EMBRYOGENESIS VIA CALLUS OF PANAX STIPULEANATUS H.T.TSAI ET K.M.FENG - Ngoc Huong, Nguyen Thi; Hung, Tran; Dep, Truong Thi (Vietnam Journal of Biotechnology, 2018)
Recently, saponins in the rhizomes of Panax stipuleanatus H.T.Tsai et K.M.Feng were studied for their effects as an anti-stress, enhancer of blood circulation and vitality, especially against human cancer cell lines. However, the number of individuals of Panax stipuleanatus H.T.Tsai et K.M.Feng in nature is threatened by the indiscriminate exploitation. High-value medicinal plants (belonging to the genus Panax) were propagated by somatic embryogenesis from the stems, leaves and petioles because of easy response to somatic embryogenesis. No report on indirect somatic embryogenesis via callus derived from the rhizomes of Panax stipuleanatus H.T.Tsai et K.M.Feng has been previously published. In this study, the callus was induced from rhizome explants on MS medium ½ macro supplemented in 2 stages with 2,4-D at high concentrations (2 mg/l in 8 weeks and then 1 mg/l in 16 weeks). The callus containing clusters of isolated and isodiametric cells were sub-cultured to a medium containing 0.5 mg /l NAA to obtain embryogenic callus. The callus growing on this medium became looser with clusters of embryonic stem cell: small size, isodiametric cell, large nucleus, clear nucleus and dense cytoplasm. The formation of clusters with homogeneous globular structures occurred at 28 weeks on medium supplemented with NAA. These embryo-like structures pass through developmental stages: late globular-shape, heart-shape, and cotyledon on medium MS medium ½ macro supplemented with 0,5 mg/l BA, 1 mg/l GA3. Besides, there were some abnormal embryos which only develop roots, shoots or just leaves.